Corporate Social Responsibility Sebagai Perwujuduan Dari Budaya Perusahaan PT. Intraco Penta, TBK - Alkornen, Faiz; Haludin, Guntur; Patih Al-Bantani, Muhammad; Daniel Christover, Wiltasar; Putra Hertianto, Ragiel (CV. Multi Kreasi Media, 2024)
This research aims to observe and find out more about the implementation of Corporate Social Responsibility and Corporate Culture in the company PT Intraco Penta, TBK. Then the method used in this research is a literature study by collecting and analyzing journal articles, websites and scientific sources that are relevant to the topic of discussion. This finding is also supported by a number of references which discuss similar matters regarding the scope or background of Corporate Social Responsibility (CSR) activities realized by PT Intraco Penta, TBK.